The Sitan-countries: History as challenge along the Silk Road - Feldbacher, Rainer (Technium Social Sciences Journal, 2021)
The Eurasian trade route was more than 6,000 kilometers long and split into several sub-strands and has a long history. Now all of these routes have been revived. With a corresponding expansion of the infrastructure, certain circumstances are still challenging in the 21st century: nationalism, especially among the former Soviet states, security in times of global terror, and economic competition. The Central Asian region is a melting pot of different ethnic groups, in ancient, as well as more recent, history, sometimes with more harmonious coexistence, and sometimes with more conflicts that influence politics and social background. The author traveled through the individual states, examined the ecological-economic factors and conducted interviews to clarify socio-political views. This paper examines the implications regarding economy and politics, the cultural background, and to where it refers.